Justification types of economic damages and lost profits caused by the violation of intellectual property rights - Pererva, P. G.; Tkachev, M. M. (Priazovskyi state technical university, 2014)
The article considers the methodological approaches to identify and study types of economic loss and loss of profits in violation of the exclusive rights. A classification criteria losses holders of counterfeit goods: direct economic losses associated economic losses, lost profits copyright owner, the copyright holder moral hazard. Grounded types of economic losses holders of each of the classifications. The main attention was paid to reducing consumer confidence in the goods and services produced with the use of a registered trademark. Proposed to consider reducing the market share, which was in the possession of the trademark holder. Defined as a loss of direct economic losses by the owner of license benefits and increase of constant cost of advertising and promotion, as well as an increase in unit costs holders logistics. The structure factors of profits attributed the shortfall in revenue or profit in two ways: by replacing parts original and counterfeit products due to disruption of the conclusion of commercial agreements with potential licensees. This group also include potential losses resulting from the total or partial failure of existing contractors from supplying products manufactured with the use of intellectual property. First consider the proposed direct economic losses holders of production excess production and related economic losses. The economic essence of the past is that the complexity of the production, sale and use of original products may affect the other products that are in some way connected with the main products.

У статті розглянуто методичні підходи до визначення та обґрунтування видів економічних збитків та упущеної вигоди при порушенні виключних прав (прав інтелектуальної власності). Запропоновано класифікаційні ознаки втрат правовласників від контрафактної продукції: прямі економічні збитки, супутні економічні збитки, упущена вигода правовласника, моральна шкода правовласника. Обґрунтовано види економічних втрат правовласників по кожній із класифікаційних ознак. Основна увага була приділена зниженню довіри споживачів до товарів та послуг, вироблених з використанням зареєстрованого товарного знаку. Запропоновано враховувати зменшення частки ринку, яка була в розпорядженні правовласника товарного знаку. Визначено в якості прямих економічних збитків недоотримання правовласником ліцензійних вигод та збільшення частки умовно-постійних витрат на рекламу та стимулювання, а також збільшення питомих витрат правовласників на логістику.. До складу факторів упущеної вигоди віднесено недоотримання доходу або прибутку в двох напрямках: за рахунок заміщення частини оригінальної продукції контрафактом та внаслідок зриву укладення комерційних угод з потенційним ліцензіатами. До цієї групи також віднесено потенційні збитки, отримані внаслідок повної або часткової відмови діючих контрагентів від поставок продукції, виготовленої з використанням об’єктів інтелектуальної власності. Вперше запропоновано враховувати прямі економічні збитки правовласників від виробництва надлишкової продукції та супутні економічні збитки. Економічна сутність останніх полягає в тому, що складнощі з виробництвом, продажами та використанням оригінальної продукції може позначитися на інших виробах, які певним чином пов’язані з основною продукцією.
Обґрунтування видів економічних збитків та упущеної вигоди, завданих порушенням прав інтелектуальної власності
Keywords: intellectual property; rights holders; rights violations; damages; lost profits; moral hazard; власність інтелектуальна; правовласник; порушення прав; збитки; шкода моральна